Academic management and meta-skills in Chinese higher education: a systematic review of graduate readiness - Chi Che; Sukanya Chaemchoy; Pruet Siribanpitak (Journal of Education and Learning (EduLearn), 2026)
This study investigates the pivotal role of academic management in promoting meta-skills development within private higher education institutions (HEIs) in Sichuan, China. Meta-skills, encompassing adaptive expertise, relational dynamics, creative agility, and strategic synthesis, are essential for equipping graduates to navigate an evolving global workforce. Utilizing a systematic review methodology, the research evaluates the influence of curriculum design, teaching strategies, and evaluation practices on meta-skills cultivation. The findings underscore the critical function of academic management in harmonizing educational strategies with workforce demands. Innovations in curriculum and pedagogy, particularly those fostering creativity, adaptability, and collaboration, emerge as key drivers for developing these competencies. This study offers actionable insights for higher education institution (HEI) administrators and policymakers aiming to enhance students’ readiness for future challenges. By integrating global educational trends with the region’s cultural and economic context, the proposed framework ensures the development of adaptable, future-ready graduates.